The Effect of Visual Media on Students' Understanding of English Vocabulary at SMPN 33 Barru - Anggi Auliya; Selma; Zulkifli; Miftahul Jannah; Rasmi; Putri Nurul Khairiyah; Abd Kadir Jaaelani (The Future of Education Journal, 2025)
This study aims to examine the effect of visual media usage on students' motivation and understanding of English vocabulary at SMPN 33 Barru. The research used a quantitative approach involving 17 ninth-grade students as the sample. Data were collected through pre-tests, post-tests, and questionnaires, and analyzed using paired t-test with the help of SPSS. The results show that visual media significantly improved students' motivation and vocabulary understanding, as evidenced by the increase in the average pre-test score from 48.71 to 80.06 in the post-test. The t-test analysis resulted in a Sig. (2-tailed) value < 0.000, indicating the effectiveness of visual media in enhancing learning outcomes.